PENGEMBANGAN OLAHRAGA REKREASI SUMATERA UTARA - Melfa Br Nababan (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to develop recreational sports in the Indonesian Community Recreational Sports Federation (FORMI) North Sumatra. The method used is descriptive qualitative using an ex post fact approach. This research includes a study conducted to examine events that have occurred and then trace back to find out the factors that can cause these events. The subject of this research is the human resources in the management of FORMI North Sumatra, namely the chairman, secretary, treasurer, and division head. Data collection techniques using data triangulation with interviews, observations, and documentation. The research is based on guidelines compiled and approved by expert validators. Data analysis in this study by means of data reduction, data presentation, and levers. Based on the results of the interviews, the results of the interview data showed that the pattern of sports coaching and development at FORMI North Sumatra had complied with the applicable provisions in the form of a coaching and development process, but the lack of good or bad absorption of community ideas that can be achieved depends on the management and government. which supports. Based on the data found by interviews and documents obtained from all activities carried out for the development of sports recreation in North Sumatra, only 30% were realized. Keywords: Development, Recreational Sports